2023
DOI: 10.1101/2023.03.07.531562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial senescence contributes to female-biased neuroinflammation in the aging mouse hippocampus: implications for Alzheimer’s disease

Abstract: Background Microglia, the brain's principal immune cells, have been implicated in the pathogenesis of Alzheimer's disease (AD), a condition shown to affect more females than males. Although sex differences in microglial function and transcriptomic programming have been described across development and in disease models of AD, no studies have comprehensively identified the sex divergences that emerge in the aging mouse hippocampus. Further, existing models of AD generally develop pathology (amyloid plaques and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(127 reference statements)
0
0
0
Order By: Relevance
“…Gender-specific responses to TREM2 in inducing disease-associated microglial states were demonstrated in earlier research (Krasemann et al, 2017). A research team found that TREM2 expression levels were higher in female aged mice compared to male mice during pathway enrichment analysis of gender-specific gene expression (Ocañas et al, 2023). Genetic polymorphisms, such as the R47H mutation, may also influence gender differences, increasing AD risks predominantly in female mice (Sayed et al, 2021).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Gender-specific responses to TREM2 in inducing disease-associated microglial states were demonstrated in earlier research (Krasemann et al, 2017). A research team found that TREM2 expression levels were higher in female aged mice compared to male mice during pathway enrichment analysis of gender-specific gene expression (Ocañas et al, 2023). Genetic polymorphisms, such as the R47H mutation, may also influence gender differences, increasing AD risks predominantly in female mice (Sayed et al, 2021).…”
Section: Summary Of Findingsmentioning
confidence: 99%